Devotion to Jesus and Historical Investigation. A Grateful, Clarifying and Critical Response to Professor Casey - Hurtado, Larry W (The Continuum Publishing Group Ltd 2004, 2004)
It is obviously very gratifying to have my recent book (Lord Jesus Christ: Devotion to Jesus in Earliest Christianity, hereafter referred to as LJC) given the attention represented in Professor Casey’s commissioned review essay. It is all the more encouraging to receive such a gracious and positive estimate of it, along with a constructive engagement with some central matters, by a scholar of Professor Casey’s stature and competence. Given the limitations of space, and in respect for Professor Casey, in what follows I shall give particular attention to the matters highlighted in his discussion.
Keywords: Lord Jesus Christ; Devotion; Early Christianity